Membandingkan Tingkat Efisiensi Metode Tsukamoto dan Sugeno untuk kasus Pneumonia - Wahyuni, Elyza Gustri (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
There are three methods that can be used to implement the Fuzzy Inference System (FIS), namely Tsukamoto, Mandani and Sugeno. Each of the three methods has its own characteristics and advantages. Several third studies used this method to compare the efficiency level of different cases. This study also aims to see the most efficient method by comparing the two FIS methods, namely Tsukamoto and Sugeno, based on medical cases from previous studies that have tested the validity of the results from pulmonary specialists. The data used are the same data as previous studies, namely regarding the diagnosis of pneumonia. The analytical method used is Mean Absolute Percantage Error (MAPE) to get the accuracy value of how close a measurement result is to the actual number. Based on the cases tested, the key from the Sugeno method resulted in a smaller MAPE than Tsukamoto, namely 3.15%, which means that the Sugeno method results closer to the pneumonia score/actual value.